Diagnosis of Perovskite Solar Cells Through Absolute Electroluminescence-Efficiency Measurements - Xue, Juanjuan; Hu, Xiaobo; Guo, Yixin; Weng, Guoen; Jiang, Jinchun; Chen, Shaoqiang; Zhu, Ziqiang; Chu, Junhao; Akiyama, Hidefumi (Frontiers in Physics, 2019)
Two organic-inorganic halide CH3NH3PbI3 perovskite solar cells prepared in the same experimental batch but having different power conversion efficiencies—18.46% and 17.15%—were investigated based on the absolute electroluminescence (EL) efficiency measurements and traditional I-V measurements. The possible factors that affect the power conversion efficiency were also investigated. Comparing the experimental I-V curves of the two solar cells, it was found that the short-circuit currents (Jsc) were nearly the same; however, the open-circuit voltages (Voc) were markedly different. Moreover, the deduced I-V curves from the absolute EL efficiencies of the two solar cells, which were mainly affected by the material quality, were almost same, proving that the device processing technology has a vital effect on Voc.